Comparative study of the healing process when using Vicryl®, Vicryl Rapid®, Vicryl Plus®, and Monocryl® sutures in the rat dermal tissue - Gartti-Jardim, Ellen Cristina [UNESP]; Souza, Ariane Paredes de [UNESP]; Carvalho, Abrahão Cavalcante Gomes de Souza [UNESP]; Pereira, Cassiano Costa Silva [UNESP]; Okamoto, Roberta [UNESP]; Filho, Osvaldo Magro [UNESP] (Springer Nature, 2012)
Introduction: Various types of sutures are available in the market with different constitutions. However, there is a lack of research to assess and quantify the behavior of these materials. Resources and materials: This study comes benchmark wires polyglactin 910 (Vicryl ®), irradiated polyglactin 910 (Vicryl Rapid ®), polyglactin 910 treated with triclosan (Vicryl Plus ®), and poliglecaprone 25 (Monocryl ®). For this, we used 40 rats that were divided into two groups, underwent two skin incisions longitudinal 2-cm long. In Group A, simple interrupted sutures using irradiated polyglactin 910 on the right and left side of polyglactin 910, and in group B, polyglactin 910 with triclosan on the right and the left poliglecaprone 25 were made. At 2, 7, 14, and 28 days after surgery, the ten animals were killed per period, and the samples were processed for histomorphologic and histometric analysis. Conclusions: The results demonstrated that the wire poliglecaprone 25 showed better biological response, with less inflammatory infiltrates and rapid organization of connective tissue. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Comparative study; Poliglecaprone; Suture; Vicryl